Clinical characteristics of bloodstream infections in adult patients with solid tumours and a nomogram for mortality prediction: a 5-year case-controlled retrospective study in a tertiary-level hospital - Xue, Lijuan; Zhu, Ying; Zong, Mingxi; Jiao, Panpan; Fu, Jianguo; Liang, Xian-Ming; Zhan, Juan (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Bloodstream infections (BSIs) are one of the leading causes of death in cancer patients. Nevertheless, the risk factors of BSIs in solid tumors have rarely been ascertained adequately. Methods: We conducted a single-center case-controlled retrospective study from 2017 to 2021 among adults with solid tumors in a tertiary-level hospital. The BSIs and control group were matched by the propensity score matching method. We found independent risk factors of occurrence and death of BSIs using univariate and multivariate regression analysis. Additionally, a nomogram was constructed to predict the risk of mortality in BSIs. Results: Of 602 patients with solid tumors in the study period, 186 had BSIs and 416 had non-BSIs. The incidence of BSIs was 2.0/1,000 admissions (206/102,704), and the 30-day mortality rate was 18.8% (35/186). Compared to the control group, the BSIs had longer hospital stays (24.5 days vs 20.0 days), and higher frequency complicating with organ failure (10.5% vs 2.4%), nephropathy (19.6% vs 3.8%), comorbidities≥3 (35.5% vs 20.0%), and liver-biliary-pancreatic infections (15.6% vs 5.3%) (all P<0.001). Among the 186 patients with BSIs, 35 died within 30 days after BSIs. Gram-negative bacteria were the most frequent microorganisms (124/192, 64.6%). Liver cancer, organ failure, a high level of lactate dehydrogenase and septic shock were the independent hazardous factors for death of BSIs. What's more, a nomogram was constructed to predict the 30-day survival rate of BSIs, which was proved to have good accuracy (AUC: 0.854; 95% confidence interval: 0.785~0923) and consistency. Conclusions: Being aware of the risk factors of BSIs redounds to take preventive measures to reduce the incidence and death of BSIs.